Gender and age differences in the global burden of peptic ulcers: an analysis based on GBD data from 1990 to 2021 - Tan, Ruirui; Zhao, Dan; Zhang, Xiaomei; Liu, Tong; Han, Chao; Li, Zhongcheng; Qi, Chenxi; Wang, Zhaohui (Frontiers in Medicine, 2025)
BackgroundPeptic ulcer (PU) is one of the most common gastrointestinal diseases worldwide. With advances in medical technology, the global disease burden of PU has been effectively controlled. However, the most recent evidence regarding the global burden of PU remains limited.MethodsUsing publicly available data from the Global Burden of Disease (GBD) study from 1990 to 2021, we analyzed the characteristics of the global burden of PU, including trends in incidence, prevalence, mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). We employed Joinpoint regression, age-period-cohort (APC) analysis, decomposition analysis, and autoregressive integrated moving average (ARIMA) modeling to evaluate changes and influencing factors for each indicator.ResultsThe global number of PU cases increased from 2,570,413 in 1990 (95% CI: 2,161,831–2,997,880) to 2,854,370 in 2021 (95% CI: 2,438,231–3,264,252), representing a cumulative growth of 11.05%. However, the age-standardized incidence rate (ASIR) decreased from 57.14 (95% CI: 48.61–66.73) per 100,000 population in 1990 to 34.10 (95% CI: 29.13–38.97) per 100,000 population in 2021. The global number of deaths due to PU decreased from 273,872 in 1990 (95% CI: 247,312–299,718) to 230,217 in 2021 (95% CI: 193,005–270,858). Significant gender differences were observed, with the disease burden consistently higher in males than in females. After controlling for period and cohort effects, the onset of PU tended to occur at younger ages, and the number of cases declined across most age groups from 1990 to 2021. The highest incidence of PU was concentrated in individuals aged 90 years and older. In terms of future trends, the global incidence of PU is projected to continue decreasing over the next 15 years. The global prevalence is expected to improve, while PU-related mortality is likely to plateau without significant increases or decreases.ConclusionThe global burden of PU has declined significantly over the past three decades. However, elderly individuals and males remain at higher risk and require continued attention in prevention and management efforts.